No added benefit of 8 weeks of shoulder external rotation strength training for youth handball players over usual handball training alone: A randomized controlled trial - Fredriksen, H.; Cools, A.; Myklebust, G. (Journal of Orthopaedic & Sports Physical Therapy, 2021)
Objective: To assess the effectiveness of a short (5-10 minutes) shoulder external rotation (ER) strength program, using elastic bands, in adolescent handball players. Design: Randomized controlled trial. Methods: The sample included 6 adolescent handball teams (3 female, 3 male) with a total of 92 players and a mean age of 16.6 years. Players were randomized within teams to an intervention group, which completed a shoulder ER strengthening program of 2 exercises performed 3 times per week after handball training for 8 weeks, or a control group of no treatment. The primary outcome was the between-group difference in shoulder ER strength change, measured as isometric strength using a handheld dynamometer from preintervention to postintervention (8 weeks). Secondary outcomes were between-group differences in internal rotation (IR) strength and the ER/IR strength ratio from preintervention to postintervention. Results: The estimated between-group difference in dominant-shoulder ER strength was 0.06 N/kg (95% confidence interval [CI]: -0.01, 0.14) in favor of the intervention group. The estimated between-group differences in the ER/IR ratio and IR strength were 0.03 (95% CI: -0.02, 0.08) and 0.02 (95% CI: -0.08, 0.13), respectively. Conclusion: The ER strength program improved neither the ER strength nor the ER:IR ratio.